The impact of visual subliminal triggers at~the point of sale on the consumers' willingness~to purchase: A critical investigation into gender differences - Ralf A. Brickau; Jasmin Cornelsen (readbox unipress, 2017)
Purpose - Over the last decades a plethora of advertising elements has been employed at the point of sale (POS) in supermarkets with the intention to increase demand among male and female consumers - with varying success. Companies still strive to understand the "black box" of consumer brains. Neuro-scientific research has brought new perspectives to consumer behaviour and shows positive results but still there are a lot of white spots on the map while trying to understand consumers' behaviour. This exploratory research is aimed at identifying gender differences in the perception of visual subliminal marketing triggers at the POS. Concentrating on food retailing, the impact of subliminal marketing triggers in the form of merchandising displays on the consumers' willingness to purchase is investigated, using the example of the confectionary product "Celebrations". Design/Methodology/Approach - Data is collected using both a quantitative and a qualitative research approach. First, a subliminal test has been conducted on a sample of 305 participants, including 154 male consumers and 151 female consumers, in order to investigate the responses of participants subjected to different subliminal advertising triggers and moreover to uncover the impact of these triggers that potentially affect the consumers' willingness to purchase. Afterwards, two focus groups divided by gender are conducted to further explore the quantitative results. One focus group consists of five male participants, while the other group comprises six female participants. The results of both approaches are submitted to a multistage analysis process. Findings - The results show that gender differences in the perception of subliminal marketing triggers exist and subsequently result in a differing general willingness to pay for the product. Regardless of the display shown, women were willing to pay more for a box of Celebrations than men. Six factors - trendy, vitality, stylish, fun/funny, dynamic and sexy - are perceived as the most important aspects of good advertising on POS-displays as they are identified positively by both genders. However, the analysis reveals that those factors are associated with different types of advertisements promoting different products. These findings indicate that men and women substantially differ in their buying behaviour as well as in their perception of advertising displays. Thus, preferences of male and female consumers in the design of advertisements are uncovered and characterized. (...)
Keywords: 650; Purchasing decision; advertising impact; gender differences; food retailing; experiment; Kaufentscheidung; Werbewirkung; Geschlechterunterschiede; Lebensmitteleinzelhandel; Experiment